2018
DOI: 10.1111/sifp.12046
|View full text |Cite
|
Sign up to set email alerts
|

Do Women Find the Progesterone Vaginal Ring Acceptable? Findings from Kenya, Nigeria, and Senegal

Abstract: The progesterone vaginal ring (PVR) is a contraceptive designed for use byC ontraceptive vaginal rings are a new product category in many developing countries. There are two contraceptive vaginal rings on the market: a three-monthly progesterone-containing ring available in a few countries in Central and South America under the brand name Progering R ; and a monthly etonogestrel/ethinyl estradiol ring sold under the brand name NuvaRing R in Europe, the United States, and other industrialized countries. Contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(53 citation statements)
references
References 20 publications
1
52
0
Order By: Relevance
“…Across studies, a smaller proportion of women reported ‘liking’ the VR (52.9 to 62.6%) [58, 79], with a higher proportion of users ‘liking’ the VR with increased duration of use [58, 75]. In observational studies, ‘satisfaction’ was mostly high, with most studies reporting satisfaction greater than 90% [29, 36, 70]. In one observational study, satisfaction was higher among women who completed at least two cycles of use compared to those who discontinued [70].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Across studies, a smaller proportion of women reported ‘liking’ the VR (52.9 to 62.6%) [58, 79], with a higher proportion of users ‘liking’ the VR with increased duration of use [58, 75]. In observational studies, ‘satisfaction’ was mostly high, with most studies reporting satisfaction greater than 90% [29, 36, 70]. In one observational study, satisfaction was higher among women who completed at least two cycles of use compared to those who discontinued [70].…”
Section: Resultsmentioning
confidence: 99%
“…In observational studies, ‘satisfaction’ was mostly high, with most studies reporting satisfaction greater than 90% [29, 36, 70]. In one observational study, satisfaction was higher among women who completed at least two cycles of use compared to those who discontinued [70]. Five contraceptive observational studies in the past decade reported that 92 to 100% of users would recommend the VR or found it acceptable [29, 36, 38, 42, 70], whereas a smaller proportion of women recommended VRs in studies from the 1980s [77, 80].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These may be more appropriate FP methods to women who are experiencing sexual violence but cannot live separately from abusive husbands. Similarly, female condoms and progesterone vaginal ring(PVR) can also enhance women’s control over their fertility [42]. However, availability and use of female condoms and PVR is very limited in Nepal [35] and needs to be promoted in future.…”
Section: Discussionmentioning
confidence: 99%
“…Both quantitative and qualitative data were collected and the results of the quantitative data analysis have been published. 10 , 11 In the quantitative study, a total of 247 women were screened across all country sites. Of these, 76% (n=189) met the eligibility criteria and provided informed consent to participate in the study.…”
Section: Introductionmentioning
confidence: 99%